Kepastian Hukum Penyelesaian Sengketa Gagal Bayar Debitur Pada Layanan Peer To Peer Lending Di Indonesia - Fahmi Budi Raharja, Ramadhan (Recital Review, 2024)
Peer to Peer lending is a form of online-based money lending service. P2P Lending has potential risks that can give rise to legal problems, namely the risk of default by the loan recipient. when the debtor default, the party who suffers the main loss is the lender. This type of thesis research uses the Normative Juridical method by taking a statutory approach and a conceptual approach. The results of the thesis research, legal certainty is achieved by using laws or regulations that are currently in effect, such as the Civil Code, Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, OJK Regulation No. 10/POJK.05/2022. legal implications received by debtors who fail to pay on P2P Lending, the debtor receives a warning from the P2P Lending organizer, the debtor is subject to sanctions in the form of fines and interest charges that continue to increase, the debtor experiences collection by collectors, recorded on a blacklist by OJK. the dispute resolution option that can be taken by creditors together with P2P Lending providers who suffer losses due to debtors' failure to pay can be pursued through non-litigation and litigation dispute resolution.